Elaboração de um plano para analisar alunos de ações afirmativas na Engenharia de Materiais através de experimento fatorial 2k - Oliveira, Cristiane Souza de (Universidade Federal de São Carlos, 2023)
The present study discusses the challenges faced by quota students from the perspective of the deficiencies in the effectiveness of Law N° 12,711/2012. Considering the intricate structure of the Brazilian educational system and the barriers hindering the advancement of underrepresented groups, this research aims to understand the aspects that influence these students' performance. Focusing on the challenges imposed by this Law, consequences such as high dropout rates, failure, and extended time to complete courses are observed. It is crucial to understand how these challenges relate to the main factors that can contribute, such as institutional inadequacy, lack of integration with the academic environment, and content gaps. Furthermore, a research proposal was developed for the Materials Engineering course at UFSCar to analyze how these impacts affect the beneficiaries of the quotas through the 2k Factorial Experiment. The importance of innovative strategies and a system that promotes equality, modernization, and acceptance of affirmative actions is emphasized. Interventions are proposed, such as partnerships, workshops, mentoring programs, and group formations, aiming to enhance inclusion and equity. The study underscores the need for effective actions to strengthen diversity and equality in higher education, reflecting on the complex structures of the Brazilian educational system and the barriers blocking the progress of underrepresented groups. In this way, the work provides a comprehensive analysis of the current scenario, delivering a solid foundation for ongoing analyses and evaluations. Moreover, it outlines a promising strategy to consolidate diversity and equality in the Materials Engineering course at UFSCar.
Elaboration of a plan to analyze affirmative action students in Materials Engineering through a 2k factorial experiment
Keywords: UFSCar; Engenharia de Materiais; Ações afirmativas; Experimento fatorial 2k; Materials Engineering; Affirmative actions; 2k factorial experiment; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS